Contemporary Nepali Arts: Ambivalence and In-between-ness - Sharma, Yam Prasad (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
Contemporary Nepali arts are connected among each other along with western arts and early Nepali artworks. These artworks share the subject matters, techniques and forms of earlier traditions. Inter-textuality is sometimes created through recycling and appropriation. Similar elements have been used for different purposes. Likewise, similar contents reappear in different forms. Contemporary Nepali arts are the mélange of various cross-currents. Ever-changing alien art influences in the present time have unsettled representational modes of arts. Some art techniques have been borrowed from the western arts, the Hindu and the Buddhist myths and rituals, and native art traditions. The artworks present different elements that have been intertwined. The artworks neither assimilate nor reject the alien art forms but strike balance between them from ambivalent and in-between space. Through the plural art forms, contemporary Nepali arts not only express the feelings of the Nepali artists but also explore the socio-cultural issues of contemporary Nepal. Due the co-presence of diverse images, symbols and forms, the artworks speak of the cultural self and the cultural other. The identities of these art forms are constructed and reconstructed in ambivalent and in-between spaces of local and global influences. Such art forms are plural and open-ended, and their significances or meanings become multiple.